PENGARUH KEPUTUSAN INVESTASI (INVESTMENT DECISIONS), RETURN ON ASSET (ROA) DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (COMPANY VALUE) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Purnasari, Nina; Lilia, Wirda; Siregar, Dewi Masnita; Simanjuntak, Karuniati Prima (Aksara Public, 2019)
The purpose of this study was to determine the effect of investment decisions, return on assets and leverage on firm value in Manufacturing Companies on the Indonesia Stock Exchange. The population in this study were all Manufacturing Companies in the Indonesia Stock Exchange, which amounted to 154 companies from 2013-2017. The sampling technique used was purposive sampling, so the final sample obtained was 67 companies. The data collection method used in this study is documentation. Sources of data in this study are secondary data obtained from financial statements of Manufacturing Companies. The data analysis technique used is the classic assumption test and multiple linear regression analysis with the help of SPSS 20 for Windows applications. Based on the results of the analysis show that investment decisions have a significant positive effect on firm value, return on assets has a significant positive effect on firm value and leverage has a significant positive effect on firm value.